2002
DOI: 10.1046/j.1525-1446.2002.19208.x
|View full text |Cite
|
Sign up to set email alerts
|

Client Perceptions of Parish Nursing

Abstract: The purpose of this study was to examine parish nursing from a client's perspective. Parish nursing is a relatively new health delivery model that has rarely been investigated. In order to describe the client perception, an ethnographic approach was used. The convenience sample included clients from two congregations in a southeastern Appalachian area served by parish nurses. Face-to-face client interviews were conducted, and the Spradley's ethnographic approach to data analysis of transcripts was used. Each i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…She describes this as the opportunity of the parish nurse to be fully present (body, heart, and soul) during a person's physical illness or suffering. Wallace, Tuck, Boland, and Witucki (2002) described the parish nurse as being available as part of presence. The theme of presence has been associated with active listening as one of the most common strategies used by parish nurses when providing care (Solari-Twadell & Hackbarth, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…She describes this as the opportunity of the parish nurse to be fully present (body, heart, and soul) during a person's physical illness or suffering. Wallace, Tuck, Boland, and Witucki (2002) described the parish nurse as being available as part of presence. The theme of presence has been associated with active listening as one of the most common strategies used by parish nurses when providing care (Solari-Twadell & Hackbarth, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Parish nursing programs, in which registered professional nurses are embedded in church congregations to provide health services and education to fellow parishioners (Anderson, 2004), represent prime examples of how religious and health organizations can collaborate to achieve the common goal of promoting health among ethnic minority LGBPs. Although churches with predominantly ethnic minority memberships have been shown to offer several social and health services, few have implemented programs that integrate formal healthcare services into the church setting (Blank et al, 2002) even though these programs are frequently perceived to be highly desirable among many minority parishioners (Madison & McGadney, 2000;Wallace et al, 2002). Thus, it would be wise for interventions to promoting parish nursing in congregations that may include ethnic minority LGBP members.…”
Section: Many Latino and African Americanmentioning
confidence: 99%
“…In numerous studies, participants have indicated that spiritual interventions are expected, desired, acknowledged, and appreciated (Bergquist & King, 1994;Burkhart, Konicek, Moorhead, & Androwich, 2005;Maddox, 2002;Wallace, Tuck, Boland, & Witucki, 2002). The most frequently documented spiritual interventions include providing spiritual support or care, facilitating coping mechanisms, assisting with grieving processes, offering presence, and being available.…”
mentioning
confidence: 99%
“…The most frequently documented spiritual interventions include providing spiritual support or care, facilitating coping mechanisms, assisting with grieving processes, offering presence, and being available. Faith community nurses also complete spiritual assessments, assist with end-of-life issues, instill hope, clarify the relationship between faith and health, use touch, encourage humor, and clarify values, taking into 300 C. I. SHORES consideration individual religious practices (Bard, 2006;Bitner & Woodward, 2004;Bokinskie & Evanson, 2009;Bokinskie & Kloster, 2008;Burkhart & Androwich, 2004;Burkhart et al, 2005;Chase-Ziolek & Iris, 2002;Coenen, Weis, Schank, & Matheus, 1999;Hinton, 2009;King & Tessaro, 2009;Koenig, 2008;Kuhn, 1997;Maddox, 2000;McCabe & Somers, 2009;McDermott & Burke, 1993;McGinnis & Zoske, 2008;Mendelson, McNeese-Smith, Koniak-Griffin, Nyamathi, & Lu, 2008;Miskelly, 1995;O'Brien, 2006;Quenstedt-Moe, 2003;Rydholm, 2006;Tuck & Wallace, 2000;Van Dover & Pfeiffer, 2007;van Loon, 1998;Wallace et al, 2002;Weis, Matheus, & Schank, 1997;Weis, Schank, Coenen, & Matheus, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation